2015
DOI: 10.1016/j.ajo.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity in Pediatric Secondary Pseudotumor Cerebri Syndrome

Abstract: Purpose To examine the clinical, demographic, and anthropometric patient characteristics of secondary pseudotumor cerebri syndrome in children and adolescents based on the recently revised diagnostic criteria. Design Retrospective observational case series. Methods Patients seen at a tertiary children's hospital for pseudotumor cerebri syndrome were classified as having either primary idiopathic (n = 59) or secondary pseudotumor cerebri syndrome (n = 16), as rigorously defined by recently revised diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 33 publications
1
35
1
2
Order By: Relevance
“…; Paley et al. ). Nandi and Biswas described one 7‐year‐old boy with bilateral isolated sixth nerve palsy and EBV mononucleosis without any sign of encephalitis (Nandi & Biswas ).…”
Section: Discussionmentioning
confidence: 99%
“…; Paley et al. ). Nandi and Biswas described one 7‐year‐old boy with bilateral isolated sixth nerve palsy and EBV mononucleosis without any sign of encephalitis (Nandi & Biswas ).…”
Section: Discussionmentioning
confidence: 99%
“…With increasing obesity in the world, the incidence of PTCS is also increasing. Before puberty, the female/male ratio is equal and secondary PTCS is commonly seen (6,7). When seen in males, secondary causes should be well researched (1).…”
Section: Discussionmentioning
confidence: 99%
“…1 There are conflicting studies explaining the anthropometrics of secondary pediatric PTCS. In one study of children with secondary PTCS, the children were obese 28 ; however, previous studies showed that the majority of children with minocyclineassociated secondary PTCS, 29 with exposure to recombinant growth hormone 30,31 or aldosteronism, 32 were not obese at presentation.…”
Section: Prepubertal Versus Postpubertal Childrenmentioning
confidence: 91%